Evaluation of the Impact of Public Service Innovation and Sustainability Model of the Family Doctor Program of the Government of the Riau Islands Province - Vyandri, Masadib Akmal; Yudiana, Tjetjep; Kusbandrijo, Bambang (Jurnal Manajemen Pelayanan Publik, 2025)
Family doctors are a regional innovation to address public health. The external aspects are successful but vulnerable in terms of sustainability. The study aims to evaluate and interpret the impact of policies and develop a sustainable model of the Family Doctor Program in the Riau Islands Province. Qualitative research approach, to understand a symptom of the impact of the program. Results; the program has a positive impact on the community and inspires the Central Government to carry out the same program. This program absorbs a lot of the APBD, is not in line with central policies on contract workers and is vulnerable to local political pressure that threatens the sustainability of the program. The model offered by the researcher is Sustainable Public Service Innovation, that good innovation begins with the presence of innovative and creative regional leaders, who are able to collaborate and coordinate well. In order for the innovation program to be sustainable, a leader must be adaptive to the development of science and technology, obey applicable legal regulations, be synergistic with local politics, and collaborate with stakeholders and optimize private sector CSR programs.